2007
DOI: 10.1002/chem.200601148
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies on Peroxide Activation by a Water‐Soluble Iron(III)–Porphyrin: Implications for OO Bond Activation in Aqueous and Nonaqueous Solvents

Abstract: The reactions of a water-soluble iron(III)-porphyrin, [meso-tetrakis(sulfonatomesityl)porphyrinato]iron(III), [Fe(III)(tmps)] (1), with m-chloroperoxybenzoic acid (mCPBA), iodosylbenzene (PhIO), and H(2)O(2) at different pH values in aqueous methanol solutions at -35 degrees C have been studied by using stopped-flow UV/Vis spectroscopy. The nature of the porphyrin product resulting from the reactions with all three oxidants changed from the oxo-iron(IV)-porphyrin pi-cation radical [Fe(IV)(tmps(*+))(O)] (1(++))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 122 publications
4
70
0
Order By: Relevance
“…These findings are consistent with the fact that under basic conditions (pH >7) the Fe(IV)-oxo form is electrochemically more stable than the Fe(IV)-oxo π* cation-radical [85]. The authors propose that under basic conditions, reaction of the Fe(IV)-oxo π* cation-radical with RO À (R¼H, CH 3 ) likely generates a reduced Fe(III)-OOR species which can then undergo homolysis to form the observed Fe(IV)-oxo intermediate or lose ROO À to reform the starting Fe(III) precursor [86].…”
Section: Reactivity Of Iron-porphyrin Intermediatessupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with the fact that under basic conditions (pH >7) the Fe(IV)-oxo form is electrochemically more stable than the Fe(IV)-oxo π* cation-radical [85]. The authors propose that under basic conditions, reaction of the Fe(IV)-oxo π* cation-radical with RO À (R¼H, CH 3 ) likely generates a reduced Fe(III)-OOR species which can then undergo homolysis to form the observed Fe(IV)-oxo intermediate or lose ROO À to reform the starting Fe(III) precursor [86].…”
Section: Reactivity Of Iron-porphyrin Intermediatessupporting
confidence: 91%
“…While it had been postulated that a mechanistic changeover was the result of acid-base effects or changes in speciation of the reacting Fe(III) complexes, it was found that the observed reactivity correlates well with the pH dependence of E '(Fe IV/III ) and E '(P +• /P) (P ¼ porphyrin). These results were interpreted to be consistent with the notion that pH-dependent redox equilibria may in fact mask the true identity of the oxidation products, especially if product analysis is the method of identification [85]. Interestingly, further investigation using rapid-scan UV-vis experiments performed at low temperature and under conditions of excess oxidant only showed formation of the Fe(IV)-oxo π* cation-radical in the pH ranges studied (pH ¼ 6.3-11.4), indicating that, for the complexes studied, O-O bond cleavage only proceeds via heterolysis when meta-chlorobenzoic acid (m-CPBA) is the oxidant [86].…”
Section: Reactivity Of Iron-porphyrin Intermediatessupporting
confidence: 81%
See 1 more Smart Citation
“…Although the corresponding Fe and Mn porphyrins have very similar rate constants for O 2 ·À dismutation, all Fe porphyrins studied by us thus far were toxic to Escherichia coli; no aerobic growth was detected in SOD-negative mutants with Fe porphyrins at levels at which analogous Mn porphyrins were fully protective (30). A loss of metal from the metal complexes during redox cycling could occur, whereby ''free'' Fe would give rise, through Fenton chemistry, to highly oxidizing · OH species; Fenton chemistry presumably occurs even if reduced iron is still bound to the porphyrin ligand (338). Thus, we limited our studies to Mn porphyrins as SOD mimics (Fig.…”
Section: B Antioxidantsmentioning
confidence: 97%
“…vary the solution acidity) to stabilize the particular high-valent oxo species in order to better comprehend the mechanistic aspects that affect the reactivity of compound I and II models for P450 [24,62,90]. 'Peroxide-shunt' reactions which resemble those of peroxidase enzyme have also been applied to 'catch' P450 compound I in order to uncover the secrets of the mechanism of its formation and its action in substrate oxidation [52,[91][92][93].…”
Section: Activation Of H2o2 By Cytochromes P450 -Biomimetic Studiesmentioning
confidence: 99%